Numerical methods for static and transient analysis of fracture mechanics problems - Wang, Peng. (2008)
In this thesis, the salient features of several approaches under the Meshless Method are distinguished. The general topics for formulation of Reproducing Kernel Particle Method (RKPM) are also reviewed. The simple static mechanics of RKPM is analyzed and the differences between the finite element method and RKPM procedures are discussed.